Comparison of dynamic change of egg selenium deposition after feeding sodium selenite or selenium-enriched yeast. (19th May 2018) - Lu, J; Qu, L; Shen, M M; Hu, Y P; Guo, J; Dou, T C; Wang, K H
ABSTRACT: The aim of this study was to compare the dynamic change of egg selenium (Se) deposition after sodium selenite (SS) or selenium-enriched yeast (SY) supplementation for 1, 3, 5, 7, 14, 21, 28, 56, and 84 d. A total of 576 32-wk-old Hy-Line Brown laying hens were randomly assigned to 3 groups (192 laying hens per group) with 6 replicates, and fed a basal diet (without Se supplementation) or basal diets with 0.3 mg/kg of Se from SS or 0.3 mg/kg of Se from SY, respectively. The results showed that the Se concentrations in the eggs from hens fed a SY-supplemented diet were significantly higher ( P < 0.001) than those from hens fed a SS-supplemented diet or a basal diet after 3 d. And the Se concentrations in the eggs from hens fed a SS-supplemented diet were significantly higher ( P < 0.001) than those from hens fed a basal diet after 14 d. There was a positive linear and quadratic correlation between Se concentrations in the eggs from hens fed a SY-supplemented diet (r 2 = 0.782, P < 0.001; r 2 = 0.837, P < 0.001) or SS-supplemented diet (r 2 = 0.355, P < 0.001; r 2 = 0.413, P < 0.001) and number of feeding days. The Se concentrations in the breasts from hens fed a SY-supplemented diet were 126.98% higher ( P < 0.001) than those from hens fed a SS-supplemented diet, and were 299.44% higher ( P < 0.001) than those from hens fed a basal diet after the 84-d feeding period. In conclusion, the dietary Se was gradually transferred into eggs with the extension of the experimental duration. The deposition rate of Se in the eggs from hens fed a SY-supplemented diet was much more rapid than that from hens fed a SS-supplemented diet, and the organic Se from SY had higher bioavailability as compared to inorganic Se from SS.